2020
DOI: 10.1200/po.19.00178
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Variants in CHEK2 Are Associated With an Adverse Prognosis in Symptomatic Early-Onset Breast Cancer

Abstract: PURPOSE Checkpoint kinase 2 ( CHEK2) is frequently included in multigene panels. We describe the associated outcomes among carriers of CHEK2 pathogenic variants in young patients with symptomatic breast cancer. PATIENTS AND METHODS Participants (N = 2,344) in the Prospective Outcomes in Sporadic Versus Hereditary Breast Cancer study had a diagnosis of primary invasive breast cancer at age ≤ 40 years. Summary statistics were used to compare tumor characteristics among CHEK2+ carriers with those who were CHEK2−.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…We also observed an association with ductal carcinoma diagnosis, which has been also demonstrated by other researchers [ 20 ], along with an increased rate, i.e., 19.2%, of contralateral breast cancer diagnoses. This is in concordance with other reports, where rates have been reported to range between 9.4–21% [ 26 , 27 , 28 ]. Furthermore, in our series, hormone therapy and/or mastectomy at primary diagnoses seem to have a positive effect on survival of CHEK2 carriers.…”
Section: Discussionsupporting
confidence: 94%
“…We also observed an association with ductal carcinoma diagnosis, which has been also demonstrated by other researchers [ 20 ], along with an increased rate, i.e., 19.2%, of contralateral breast cancer diagnoses. This is in concordance with other reports, where rates have been reported to range between 9.4–21% [ 26 , 27 , 28 ]. Furthermore, in our series, hormone therapy and/or mastectomy at primary diagnoses seem to have a positive effect on survival of CHEK2 carriers.…”
Section: Discussionsupporting
confidence: 94%
“…A recent study has suggested that patients with invasive breast cancer carrying the c.1100delC mutation are more likely to be obese, though this is not the case for the general population ( Greville-Heygate et al , 2020 ). Thus, when we tested for such an interaction between PCOS, c.1100delC, and obesity using a logit regression model, a P -value of 0.066 for c.1100delC-BMI interaction was obtained (OR 1.04, 95% CI 0.99–1.09).…”
Section: Resultsmentioning
confidence: 99%
“…We tested whether an interaction between c.1100delC mutation, obesity and PCOS could be detected, as such a phenomenon has been identified between the mutation carriers in invasive breast cancer ( Greville-Heygate et al , 2020 ). We fitted a logistic model where PCOS was the outcome, the lead variant genotype and BMI formed the interaction term, and the 10 first genetic PCs along with age were added as covariates.…”
Section: Methodsmentioning
confidence: 99%
“…and Finnish (0.029) populations, compared to the Non-Finnish, North-Western European population (0.002) according to the gnomAD database [55]. The enrichment of the alleles likely allowed us to detect the associations with PCOS in the Finnish and Estonian populations, whereas in populations with lower minor allele frequencies, much larger study populations would need to be used.…”
Section: Discussionmentioning
confidence: 99%